Fluids in acute kidney injury - Uma Ali (Wolters Kluwer Medknow Publications, 2018)
Early restoration of euvolemia is the initial step in the management of critically ill children and is important for preventing acute kidney injury(AKI). Isotonic crystalloids are the preferred solutions for fluid resuscitation. Repeated boluses of normal saline may lead to hyperchloremia, renal vasoconstriction and renal injury. Balanced solutions have a physiological advantage and there is evidence to suggest that resuscitation with balanced solutions may be associated with lower incidence of AKI. Synthetic colloids such as starches cause renal injury and should be avoided. Albumin can be used judiciously along with crystalloids to limit fluid overload. Fluid resuscitation alone prevents AKI only in 50% of the critically ill patients. Fluid overload as well as rapid fluid administration may adversely affect the kidney through injury to the glycocalyx. It may lead to intrarenal edema and a compartment-like syndrome compromising renal perfusion. Repeat fluid bolus should only be given when there is evidence of ongoing hypoperfusion and the bedside hemodynamic assessment suggests fluid responsiveness, provided the patient is not at high risk for fluid overload. Moderate fluid resuscitation combined with pressors may restore renal perfusion better than fluids alone. In established AKI, diuretics have a limited role. Timely institution of renal replacement therapy leads to optimum fluid management. Overzealous fluid removal should be avoided to prevent hypovolemia and recurrent renal injury.